The Impact of Human Resource Development on Bawaslu Performance in Supervising the 2024 Simultaneous Elections - Ependi Pasaribu; Sri Indarti; Lailan Tawila Berampu; Samsir (LPPM Institut Bisnis dan Informatika Kesatuan, 2026)
This article examines how human resource development influences the performance of election supervisory bodies (Badan Pengawas Pemilu/Bawaslu) at the regency/city level in North Sumatra Province during the 2024 Simultaneous Elections, a region characterized by high socio-political complexity. The study aims to identify key human resource strategies that contribute to effective electoral supervision and dispute prevention. Using a systematic literature review of academic publications, scholarly books, and official Bawaslu reports published between 2006 and 2025, with emphasis on studies from 2020–2025, the analysis is complemented by secondary data on election result disputes submitted to the Constitutional Court. Content analysis reveals four strategic pillars of human resource development: continuous training and technical guidance, multi-level mentoring and supervision, utilization of information technology for real-time reporting, and reinforcement of integrity and professionalism. The findings indicate that the integration of these pillars enhances supervisory capacity in preventing violations, managing disputes, and ensuring accountability. This is reflected in the limited number of election dispute cases, with most applications dismissed and only one case related to administrative compliance rather than supervisory weakness. Overall, the study demonstrates that comprehensive human resource development plays a crucial role in strengthening supervisory performance and supporting democratic credibility at the local level.